A portrait of cold gas in galaxies at 60pc resolution and a simple method to test hypotheses that link small-scale ISM structure to galaxy-scale processes - Leroy, Adam K.; Kruijssen, Diederik (Arxiv, 2016)
The cloud-scale density, velocity dispersion, and gravitational boundedness of the interstellar medium (ISM) vary within and among galaxies. In turbulent models, these properties play key roles in the ability of gas to form stars. New high fidelity, high resolution surveys offer the prospect to measure these quantities across galaxies. We present a simple approach to make such measurements and to test hypotheses that link small-scale gas structure to star formation and galactic environment. Our calculations capture the key physics of the Larson scaling relations, and we show good correspondence between our approach and a traditional "cloud properties" treatment. However, we argue that our method is preferable in many cases because of its simple, reproducible characterization of all emission. Using, low-J 12CO data from recent surveys, we characterize the molecular ISM at 60pc resolution in the Antennae, the Large Magellanic Cloud, M31, M33, M51, and M74. We report the distributions of surface density, velocity dispersion, and gravitational boundedness at 60pc scales and show galaxy-to-galaxy and intra-galaxy variations in each. The distribution of flux as a function of surface density appears roughly lognormal with a 1sigma width of ~0.3 dex, though the center of this distribution varies from galaxy to galaxy. The 60pc resolution line width and molecular gas surface density correlate well, which is a fundamental behavior expected for virialized or free-falling gas. Varying the measurement scale for the LMC and M31, we show that the molecular ISM has higher surface densities, lower line widths, and more self-gravity at smaller scales.
Gesehen am 30.10.2017